Lutter au quotidien - Charif Elalaoui (Temporalités)
In order to understand what is at stake in the daily struggle of the Yellow Vests and the transformation of identifications it brings about, we propose to analyze the way in which the temporalities of the yellow event structure the daily lives of the protagonists and punctuate family temporalities, and those linked to work and leisure. We will follow the deep mutations of their form of engagement, the appropriation of militant practices as the days and weeks of this sequence of protest progress, as well as the long processes of disintegration of the movement that will lead to the disappearance of certain localized social configurations The article is based on a localized research that lasts since November 17, 2018. From a bottom reading, we focus particularly on the militant trajectories of some Yellow Vests. These protagonists present three characteristics: the duration of their mobilization; the centrality of some of them in the daily struggle; and finally their belonging to the working classes.